Polypropylene/Luffa Wood Plastic Composites with High Fibre Loading - Nur ‘Aisyah Umar Syarifuddin, Siti; Roslan Raja Mohamed, Raja; Faiza Mohd, Ahmad; Zaharah Engku Zawawi, Engku; Hikamah Seth, Nur; Kamarun, Dzaraini (International Journal of Engineering and Technology, 2018)
Conventionally, wood plastic composites (WPC) utilize wood fibres from timber industry waste as the source of natural fibres (NF). Non-wood fibres may contribute as an alternative source of fibres for WPC industries. Non-wood fibres such as those from kenaf, sugarcane, hemp, sisal and flax plant offer several advantages over wood fibres in terms of shorter maturation time and ease of planting and harvesting; hence greater sustainability. However, reported researches on non-wood NF plastics composites are confined to loadings of fibres less than 50%; diminishing their marketability as ‘green’ products. ‘Green’ WPC products should incorporate a minimum of 50% NF (biodegradable component) in order for it to be readily recognized and accepted by consumers and trade holders. This paper discussed the development of a WPC based on luffa fibre with loadings of up to 65%. Luffa fibre originates from the matured fruits of luffa plants locally planted for food consumption before maturation. Polypropylene was selected as the polymer matrix due to its low cost and good mechanical properties compared to other thermoplastics such as PE and PVC. Four formulations of PP/luffa were developed at 50, 55, 60 and 65 % fibre loading and test pieces were prepared using an injection molding machine. Formulations of the composite included maleic anhydride grafted polypropylene (MAPP) as coupling agent and Cloisite 15A as fillers. Tensile, impact and fracture properties were determined and compared with several wood-based WPCs reported in the literature. The impact and fracture properties are comparable if not better than the wood-based WPCs. The tensile strength is however lower than the cited wood-based WPCs probably due to inhomogeneity and insufficient distribution of fillers in the PP/luffa composites. As a conclusion, PP/luffa WPC has the potential to be used as an alternative injection molded ‘green’ WPC product with properties comparable to wood-based WPC; and added advantage of greater sustainability.
Keywords: green composites; luffa; non-wood fibres; wood fibres; wood plastic composites.